Peak antibody production is associated with increased oxidative metabolism in an industrially relevant fed‐batch CHO cell culture1. Issue 7 (4th March 2013) - Templeton, Neil; Dean, Jason; Reddy, Pranhitha; Young, Jamey D.
Abstract Cell metabolism can vary considerably over the course of a typical fed‐batch antibody production process. However, the intracellular pathway alterations associated with various phases of growth and antibody production have yet to be fully elucidated using industrially relevant production hosts. Therefore, we performed 13C labeling experiments and metabolic flux analysis (MFA) to characterize CHO cell metabolism during four separate phases of a fed‐batch culture designed to closely represent industrial process conditions. First, we found that peak specific growth rate was associated with high lactate production and minimal TCA cycling. Conversely, we found that lactate metabolism switched from net production to net consumption as the culture transitioned from peak growth to peak antibody production. During the peak antibody production phase, energy was primarily generated through oxidative phosphorylation, which was also associated with elevated oxidative pentose phosphate pathway (oxPPP) activity. Interestingly, as TCA cycling and antibody production reached their peaks, specific growth rate continued to diminish as the culture entered stationary phase. However, TCA cycling and oxPPP activity remained high even as viable cell density began to decline. Overall, we found that a highly oxidative state of metabolism corresponded with peak antibody production, whereas peak cell growth was characterized by a highly glycolytic metabolic state. Biotechnol. Bioeng. 2013; 110: 2013–2024. © 2013 Wiley Periodicals, Inc.